Analysis of a balanced safety performance indicator as a key element of operational controlling in the ATS organization - R. A. Obraztsov; V. D. Sharov (Научный вестник МГТУ ГА, 2024)
Controlling is considered as a versatile modern focus of management. It is widespread in various fields of human activity but has not found direct application in civil aviation yet. Meanwhile, any aviation organization is subject to the general laws of management, therefore, controlling can and should find its application in the management of an aviation organization. Due to the particular importance of safety management considerations, controlling, as a management concept that allows you to control processes rather than results, fits seamlessly into the procedures of safety management systems (SMS) of aviation service providers. In particular, the development and monitoring of safety performance indicators (SPI) can be considered as a key element of operational controlling. In the SMS, the procedure to deal with the SPI, in conjunction with the risks mitigation procedure for safety, is an essential component of the entire system. To ensure the effectiveness of this procedure in the Air Traffic Service (ATS) organization, it is necessary to develop a balanced overall SPI. As the analysis showed, the indicators applicable in ATS organizations are focused on considering only incidents of the same “weight” and do not objectively reflect a level of safety assurance at ATS and its dynamics. The article presents a variant of developing a revised balanced indicator, which considers less significant deviations from the proper ATS system operation, errors and violations of personnel. The indicator was developed on the basis of the expert survey of ATS specialists. Monitoring and predicting of indicators are also important tasks of operational controlling. These problems can be solved by various methods, the applicability and comparative effectiveness of some of them are discussed in this article. All calculations are based on real data of one of the major ATS organizations of the Russian Federation.